2011
DOI: 10.1093/bioinformatics/btr638
|View full text |Cite
|
Sign up to set email alerts
|

PSICOV: precise structural contact prediction using sparse inverse covariance estimation on large multiple sequence alignments

Abstract: The PSICOV source code can be downloaded from http://bioinf.cs.ucl.ac.uk/downloads/PSICOV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
893
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 747 publications
(912 citation statements)
references
References 41 publications
5
893
0
1
Order By: Relevance
“…Previous work (2)(3)(4) has demonstrated that contacts between residues in the 3D structure of a protein can be predicted with considerable accuracy for large protein families based on the evolutionary covariance observed in multiple sequence alignments. We briefly review the basis for these approaches to motivate the method described in this paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work (2)(3)(4) has demonstrated that contacts between residues in the 3D structure of a protein can be predicted with considerable accuracy for large protein families based on the evolutionary covariance observed in multiple sequence alignments. We briefly review the basis for these approaches to motivate the method described in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…DCA, PSICOV and PLMDCA reweigh sequences in the input multiple sequence alignment to account for redundancy (2,3,6). When making predictions using GREMLIN, we reweigh sequences in a filtered alignment (filtered at 90% sequence identity) instead of using the full alignment.…”
Section: Svmcon We Used Svmcon With the Default Settingsmentioning
confidence: 99%
“…Previous studies have developed a number of techniques to do this (Mézard and Mora 2009;Weigt et al 2009;Balakrishnan et al 2011;Cocco and Monasson 2011;Morcos et al 2011;Haq et al 2012;Jones et al 2012;Ekeberg et al 2013;Ferguson et al 2013;Barton et al 2016a). Following Ferguson et al (2013), we estimate the bivariate marginals given a set of fields and couplings by generating sequences through Markov Chain Monte Carlo (MCMC) where the Metropolis criterion for a generated sequence is proportional to the exponentiated Potts Hamiltonian.…”
Section: Model Inferencementioning
confidence: 99%
“…However, these methods ignore the transitive correlation between residues and thus generate many false positive results. The inverse covariance matrix and pseudo-likelihood maximization were introduced subsequently to eliminate transitivity in methods such as DCA [12], PSICOV [13], plmDCA [14], GREMLIN [15], CCMpred [16], FreeContact [17] and PconsC2 [18]. These methods effectively reduce false positive predictions by globally considering all inter-residue correlations.…”
Section: Author Summarymentioning
confidence: 99%